In Vitro Evaluation of Shear Bond Strength with OrthGuide Computer-Aided Indirect Bonding Variables: Tray Design Versions and Composite Texture (Latakia University Journal -Medical Sciences Series, 2025)
Objective: This laboratory study aims to conduct a comparison between two indirect adhesive methods that share modern computer-assisted design and manufacturing with regard to measuring the ability of orthodontic brackets to resist shear forces applied to them during the treatment period , in addition to investigating the existence of a correlation between the quality of the adhesive used and its ability to reach the top resistant to the aforementioned forces.Materials and Methods: The research sample consisted of 60 newly extracted upper premolars that were distributed into 4 groups according to the method of designing the orthodontic bracket molds and the type of adhesive material used in them. American mini master 0.022 MBT brackets were affixed to all of them using 3D printed resin holders and trays of Thermally plasticized polyvinyl siloxane, using two types of light curing composites and dual curing ones. Then, the resistance of these adhesive brackets to shear forces was tested through a set of appropriate laboratory tests.Results: The results of this study showed that the greatest value of resistance to shear bond strength was in the group of brackets affixed via 3D printed resin holders and light cured composite, while there were no significant differences between the rest of the groups.Conclusions: Bonding metal orthodontic brackets using 3D-printed holders produced sufficient bond strengths to meet clinical needs. Also, brackets bonded to thermoplastic trays did not show adequate strength when it tested, even with the use of two types of adhesive materials in the study.
Keywords: 3D printed resin trays , Transparent thermoplastic holders , Dual curing composite, Shear bond strength